2012
DOI: 10.1097/dad.0b013e3182448f7c
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Toll-Like Receptor Activity in Different Stages of Cutaneous T-Cell Lymphoma

Abstract: It is known that human keratinocytes (KCs) express Toll-like receptors (TLRs). However, published reports conflict regarding TLR expression in cutaneous T-cell lymphoma patient's KCs. To define the pattern of expression and detect any differences of TLRs 1-9 and p65 expression in epidermal KCs, tumor infiltrate, and endothelial cell types using immunohistochemical stains on fixed and paraffin-embedded sections of mycosis fungoides (MF) in patch, plaque, and nodular stages. MF cases showed no change in pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Kado et al ., using immunohistochemical staining for TLR7 expression, showed that staining for TLR7 was strongest in tumour infiltrate staining. This increased staining was particularly interesting with regard to tumour stage as these lymphocytes were thought to represent primarily malignant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kado et al ., using immunohistochemical staining for TLR7 expression, showed that staining for TLR7 was strongest in tumour infiltrate staining. This increased staining was particularly interesting with regard to tumour stage as these lymphocytes were thought to represent primarily malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their results possibly indicated that fragmentation of the malignant cell chromosomes into single‐stranded RNA, a frequent finding in neoplasias, might be the activating ligand inducing that antitumor‐type phenomenon, which is further enhanced by synthetic imidazoquinoline application. TLR7 upregulation might be due to the body attempting to mount an antitumor response or, because of decreased functionality, creating further immune dysregulation and lack of immune surveillance …”
Section: Discussionmentioning
confidence: 99%
“…Além das evidências histológicas de regressão de lesões, há uma diminuição do número de células T reguladoras Foxp3+ e aumento de pDCs(64).Um outro estudo evidenciou em biópsias de pele de pacientes com MF o aumento da expressão de TLRs 2, 4 e 9(65). Nos vasos dérmicos, a presença de TLRs 4, 5 e 6 pode determinar um possível papel na sinalização de linfócitos na pele ou uma regulação positiva de mediadores inflamatórios que atuam durante o ciclo da doença(66).Esses dados salientam a importância de estimular a resposta inata, seja por imidazoquinolinas ou CpG, em combinação com modificadores biológicos, para potencializar a resposta imune de pacientes com LCCT em estágio avançado (eritrodermia e células T malignas circulantes). Além disto, a utilização dos adjuvantes em fases iniciais da doença pode ser uma estratégia para prevenir a anergia da resposta imunológica no LCCT.…”
unclassified